Phát triển năng lực công nghệ cho học sinh thông qua dạy học trải nghiệm môn Công nghệ: Một nghiên cứu tổng quan - Bùi Thị Hải Yến, Bùi Thị Hải Yến; Nguyễn Tất Thắng, Nguyễn Tất Thắng; Trương Thị Hoa, Trương Thị Hoa (Tạp chí Giáo dục, 2026)
In the context of general education reform and the requirements of the 2018 General Education Curriculum, technological competence is defined as a domain-specific competence, with Technology education playing a central role delivered through an experiential learning orientation. This article synthesizes and analyzes domestic and international studies on developing students’ technological competence through experiential learning in Technology education to identify prevailing research approaches and remaining research gaps. The study adopts a narrative literature review of 39 publicationsthat met the inclusion criteria of direct topical relevance, full-text availability, and demonstrable scholarly quality. Sources comprise journal articles, books/book chapters, dissertations, and other scholarly outputs, retrieved via scholarly search platforms (e.g., Google Scholar) and repositories (e.g., ResearchGate). Search terms included “technology,” “technological competence,” “technology education,” “general education,” “technology in general education schools,” and “experiential learning.” The review delineates directions for future research to support ongoing pedagogical innovation in Technology education.